FarmX - Tala Yaseen; Samaa Yasin (My University, 2025)
Agriculture remains a vital sector in Palestine, supporting livelihoods and food security. How- ever, farmers face numerous challenges, including inefficient traditional practices, limited tech- nological access, and weak connections with consumers. FarmX is a smart, web- and mobile- based farm management system designed to address these issues. The platform provides a comprehensive ecosystem for farmers to manage their farms, track planted crops, and sell prod- ucts directly to consumers through an integrated digital marketplace. The system supports multiple user roles, including farmers, consumers, administrators, and order handlers. It features a 3D interactive homepage, real-time communication using Firebase, and personalized notifications. FarmX was developed using Spring Boot for backend services, React and Next.js for the web interface, and React Native for the mobile application. The platform integrates modern technologies to enhance agricultural productivity, foster community interaction, and support sustainable development. This project demonstrates how software engineering can be applied to empower local farmers and revolutionize agricultural systems in the region